KAJIAN EMISI DAN KONSUMSI BAHAN BAKAR DALAM PENGGUNAAN CAMPURAN BAHAN BAKAR BIOSOLAR PADA KENDARAAN PENUMPANG - Budi Rochmanto; Hari Setiapraja; Mutia Ekasari (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2020)
Research has been conducted to determne the effect of using biodiesesl on emission and fuel efficiencyin diesel engine vehicle. Testing was conducted on vehicle 2500 cc fuelled with 2 base fuel of diesel fuel 48 and diesel fuel Euro4 standard in which both of base fuel was blended with biofuel in form of FAME and HVO with ratio of 30% (B30). Test method was using United Nations Economic Commission for Europe, yakni UN ECE R83 and R10. The results showed the addition of 30% FAME and 30% HVO in petrodiesel and diesel fuel 48, was able to reduce CO and HC emissions. While for NOx emissions there has not been a significant change. The addition of FAME to both base fuels was able to reduce particulate emissions, but conversely with the addition of HVO, particulate emissions were higher. The addition of FAME and HVO to petrodiesel has not been able to save fuel consumption, instead there was a slight increase of 0.1% for FAME and 0.5% HVO. Meanwhile for diesel fuel 48 the addition of FAME is more economical around 5.5%, while the addition of HVO is a little extravagant around 1.8%.%.